Current Practices in Ileal Pouch Surveillance for Patients With Ulcerative Colitis: A Multinational, Retrospective Cohort Study. (24th December 2018) - Samaan, Mark A; Forsyth, Katrina; Segal, Jonathan P; De Jong, Djuna; Vleugels, Jasper L A; Elkady, Soad; Kabir, Misha; Campbell, Samantha; Kok, Klaartje; Armstrong, David G; Penez, Lawrence; Arenaza, Aitor P; et al.
Abstract: Background and Aims: There are no universally accepted guidelines regarding surveillance of ulcerative colitis [UC] patients after restorative proctocolectomy and ileal pouch-anal anastomosis [IPAA]. There also exists a lack of validated quality assurance standards for performing pouchoscopy. To better understand IPAA surveillance practices in the face of this clinical equipoise, we carried out a retrospective cohort study at five inflammatory bowel disease [IBD] referral centres. Methods: Records of patients who underwent IPAA for UC or IBD unclassified [IBDU] were reviewed, and patients with <1-year follow-up after restoration of intestinal continuity were excluded. Criteria for determining the risk of pouch dysplasia formation were collected as well as the use of pouchoscopy, biopsies, and completeness of reports. Results: We included 272 patients. Median duration of pouch follow-up was 10.5 [3.3–23.6] years; 95/272 [35%] had never undergone pouchoscopy for any indication; 191/272 [70%] had never undergone pouchoscopy with surveillance as the specific indication; and 3/26 [12%] high-risk patients had never undergone pouchoscopy. Two cases of adenocarcinoma were identified, occurring in the rectal cuff of low-risk patients. Patients under the care of surgeons appeared more likely to undergo surveillance, but rates of incomplete reporting were higher among surgeons [78%] than gastroenterologists [54%, p = 0.002]. Conclusions: We observed wide variation in surveillance of UC/IBDU-IPAA patients. In addition, the rate of neoplasia formation among 'low-risk' patients was higher than may have been expected. We therefore concur with previous recommendations that pouchoscopy be performed at 1 year postoperatively, to refine risk-stratification based on clinical factors alone. Reports should document findings in all regions of the pouch and biopsies should be taken.